2015
DOI: 10.1111/micc.12219
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Arterial Hypertension and Age on the Sublingual Microcirculation of Healthy Volunteers and Outpatients with Cardiovascular Risk Factors

Abstract: Preexistent chronic arterial hypertension was associated with lower vascular densities. In contrast, age showed no effect on sublingual microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
(64 reference statements)
0
24
0
Order By: Relevance
“…measured the pulsatile ocular blood flow of diabetic patients, and the results suggested that subjects with systemic hypertension had an increased blood flow rate compared to controls without hypertension. In contrast, Kanoore Edul et al . said that there was no correlation between BP and blood flow in the sublingual microcirculation.…”
Section: Discussionmentioning
confidence: 94%
“…measured the pulsatile ocular blood flow of diabetic patients, and the results suggested that subjects with systemic hypertension had an increased blood flow rate compared to controls without hypertension. In contrast, Kanoore Edul et al . said that there was no correlation between BP and blood flow in the sublingual microcirculation.…”
Section: Discussionmentioning
confidence: 94%
“…In a parallel observation, hypertensive patients had a lower sublingual capillary TVD than healthy controls unless they were exercising for at least 150 min week –1 , in which case they reached levels of TVD similar to those of healthy controls (Kanoore Edul et al . ). Also in patients with chronic mesenterial ischaemia, a lower TVD was found than in healthy controls, which increased in value upon caloric challenge, whereas healthy controls presented the same higher level of TVD at baseline, remaining unchanged after caloric challenge (Harki et al .…”
Section: Discussionmentioning
confidence: 97%
“…Patients with active infections and bleeding were excluded. Cirrhotic patients were compared to the same number of noncirrhotic volunteers individually matched for age, sex, and cardiovascular risk factors . One‐year mortality was registered.…”
Section: Methodsmentioning
confidence: 99%